Odious Debts: Issues in Law and Politics - Wong, Yvonne (Indonesian Journal of International Law, 2021)
Odious sovereign contracts inhibit developing country growth. They cause money and resources to be improperly transferred from one country to an undeserving one. Think tanks and civil society actors have long suggested that Indonesia is plagued by a sizeable odious sovereign contract account. Policy makers and scholars continue to grapple with how the odious debts doctrine may operate in law to curb this important problem. Taking into account the lack of transparency in an odious contract setting, this paper proposes a new approach premised on principles of transparency, accountability and citizen participation in public contracts. In design, it proposes the following: 1) the creation of ex-ante obligations and a public website on which financiers can disclose the key terms of their contractual arrangements with a sovereign government. This website enables a financier to signal the nature of their engagement with a sovereign counterpart; 2) the creation of an ex-post tribunal, in which private citizens have standing, to adjudicate the odiousness of a disputed sovereign contract. In the tribunal’s deliberations, disclosure by a financier and compliance with ex-ante obligations weighs in favour of a presumption of legitimate contracting, whereas non-disclosure lends itself to a presumption of odiousness. This new approach has the right incentives for participation. It will revolutionize the currency of international law and international institutions, by giving the public a mechanism to eke out odiousness in transnational sovereign dealings. It can have important implications for Indonesia and more generally, the future of transnational trade and finance.